Placental Mesenchymal Stromal Cells (PMSCs) and PMSC-Derived Extracellular Vesicles (PMSC-EVs) Attenuated Renal Fibrosis in Rats with Unilateral Ureteral Obstruction (UUO) by Regulating CD4+ T Cell Polarization - Zhu Zhu; Chaonan Han; Shuli Xian; Feng Zhuang; Feng Ding; Wei Zhang; Yingli Liu (Hindawi Limited, 2020)
Purpose. Recent evidence has shown that CD4+ T helper (Th) cells are involved in renal inflammation and fibrosis. However, whether renal fibrosis can be alleviated by intervening in the polarization of CD4+ T cells remains unknown. Our research investigated the effects of intravenously administered placenta mesenchymal stromal cells (PMSCs) or treatment with extracellular EVs (EVs) derived from PMSCs (PMSC-EVs) on the polarization of CD4+ T cells in rats with unilateral ureteral obstruction (UUO). We further verified how PMSCs affect inflammatory factor secretion and the levels of regulatory T (Treg) and Th17 CD4+ T cells in vitro. Materials and Methods. We evaluated renal interstitial inflammation and fibrosis by pathological section staining, tested the polarization of CD4+ T cells (Th17 and Treg phenotypes) by flow cytometry (FCM) and immunohistochemistry, and detected the cytokines secreted by CD4+ T cells by enzyme-linked immunosorbent assay (ELISA). Results. Compared with that of control rats, the renal tissue of PMSC-treated rats exhibited lower renal Masson scores and more Foxp3+ cell infiltration, with a significantly decreased IL17A+CD4+ T cell/CD4+ T cell ratio and a significantly elevated anti-inflammatory cytokine (IL-10) level. When CD4+ T cells were cocultured with PMSCs, CD4+IL17A+ cell percentages were decreased in a UUO model after 7 days of coculture with PMSCs. The secretion of TGF-β and IL-10 was significantly increased (P<0.05), while the secretion of IFN-γ, IL-17, and IL-6 was significantly decreased (P<0.05) in the PMSC coculture group. Moreover, after treatment with PMSC-EVs, tubulointerstitial fibrosis was alleviated, and Foxp3+/IL-17+ cell infiltration was increased in the kidneys of UUO model animals on day 7. Conclusions. PMSCs can convert the inflammatory environment into an anti-inflammatory environment by affecting the polarization of CD4+ T cells and macrophages, inhibiting the inflammatory factors IFN-γ and IL-17, and upregulating the expression of the anti-inflammatory factors TGF-β and IL-10, ultimately leading to renal protection. Such functions may be mediated by the paracrine activity of PMSC-EVs.